Graph operations on Cayley graphs of semigroups - Assari, Amir; Hosseinzadeh, Narges (International Journal of Applied Mathematical Research, 2014)
Lots of large graphs can be constructed from existing smaller graphs by using graph operations, such as the graph products. Many properties of such large graphs are closely related to those of the corresponding smaller ones.In this paper we consider some operations of Cayley graphs on semigroups. Keywords: Graph operation, Cyaley graph, Col-Aut-vertex transitive.